Effect of Glass Fiber Post Diameter on Fracture Resistance of Endodontically Treated Teeth - Saied Nokar; Mahsa Sadat Mortazavi; Somayeh Niakan (Association of Support to Oral Health Research (APESB), 2022)
Objective: To determine the fracture resistance of endodontically treated teeth restored with three different diameters of glass fiber posts and metal-ceramic crowns. Material and Methods: Thirty human maxillary canines were selected and subjected to root canal therapy. The teeth were randomly divided into three groups of glass fiber posts with 1.4 mm diameter (Group I), 1.6 mm diameter (Group II), and 2.0 mm diameter (Group III). The teeth were restored with metal-ceramic crowns and subjected to the compressive load applied at 45° angle to the longitudinal axis until fracture. The mode of failure was determined. Data were analyzed using ANOVA, followed by Tukey's post hoc multiple comparisons test (p<0.05). Results: The mean fracture resistance of groups I, II and III was 574 ± 91.2 N, 617 ± 85.21 N and 467 ± 99.43 N, respectively. No significant difference was noted between groups I and II, while the fracture resistance was significantly different between groups I and III (p<0.05) and groups II and III (p<0.05). No case of post fracture alone occurred in any group. Conclusion: The diameter of glass fiber posts can affect the fracture resistance of teeth. Based on the results, increasing the diameter of the post up to 1.6 mm may increase the fracture resistance of root, although excessive diameters are not recommended.